Pengembangan E-Modul Stoikiometri Berbasis Discovery Learning sebagai Bahan Ajar Pendukung Pembelajaran Kimia Kelas X - Darlin, Dinda Malayka Anjani; Hanifah, Sarina; Astuti, Tiwi Nur (Universitas Muhammadiyah Magelang, 2026)
This study aimed to develop a Discovery Learning-based Stoichiometry e-module that is feasible to be used as a supporting instructional material for Grade X chemistry learning. The research employed a Research and Development (R&D) method using the ADDIE model, which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. Data were collected through teacher interviews, student needs analysis questionnaires, expert validation sheets, and student response questionnaires administered in a limited trial involving 30 Grade X students. The data were analyzed to determine the validity, reliability, and feasibility of the developed teaching material.The results showed that the e-module achieved a content validity score of 0.95, categorized as highly valid. The construct validity test indicated that all instrument items were valid (r-count > r-table 0.361) and reliable, with a Cronbach’s Alpha value of 0.95 (> 0.70). The limited trial results revealed a feasibility level of 78.17%, categorized as highly feasible. Therefore, the Discovery Learning-based Stoichiometry e-module is considered suitable as a supporting instructional material that helps students understand stoichiometric concepts in a more structured, active, and meaningful learning.